Kenneth MacMillan's Romeo and Juliet - Prokofʹev, Sergej Sergeevič 1891-1953 (Opus Arte, 2021)
Kenneth MacMillan's passionate choreography for Romeo and Juliet shows The Royal Ballet at its dramatic finest. Sergey Prokofiev's famously evocative score is the driver for some of the most ardent pas de deux and powerful set pieces in ballet history. The vibrant crowd scenes with magnificent designs by Nicholas Georgiadis vividly recreate the color and bustle of sixteenth-century Verona in this Royal Ballet classic
Bildformat: 16:9
Aufnahme: London, Covent Garden, Royal Opera House, 1./11. Juni 2019
Enthält Bonusmaterial
Keywords: Ballets; Filmed ballets; Filmed performances; Film; DVD-Video